Opinions of Oriental Scholars on Speech Development in Mother Language Education - Kurbanova Kholbibi Kirboyevna (Genius Journals, 2023)
In this article, the development of speech in the process of mother tongue education, the requirements for the student's speech, the opinions of the great scholars of the East about the development of speech, and their great contributions to the creation of the methodology of speech acquisition. In the process of mother tongue education, the issues of the important pedagogical necessity of learning oral and written speech, learning speech in connection with behavior and manners are highlighted
Keywords: speech; speech activity; text; creativity